Numerical investigation on the effect of reactivity gradient in an RCCI engine fueled with gasoline and diesel. (1st March 2015) - Li, J.; Yang, W.M.; An, H.; Zhou, D.Z.; Yu, W.B.; Wang, J.X.; Li, L.
Highlights: A chemical reaction mechanism is newly developed for dual fuel combustion. The developed chemical kinetics is coupled with KIVA4 to model the combustion. The role of reactivity gradient in RCCI combustion is investigated. The RCCI (dual fuel mode) combustion is compared with blend fuel mode. Abstract: The reactivity controlled compression ignition (RCCI), which belongs to dual fuel mode (DFM) combustion has been considered as a promising way to achieve high fuel conversion efficiency and low emissions. By this strategy, a fuel reactivity gradient is formed in the combustion chamber which offers the probability of controlling combustion phasing. In this study, the role of fuel reactivity gradient was examined numerically by comparing a DFM (i.e., RCCI) combustion with other hypothetical cases under one specific load condition. Firstly, a chemical reaction mechanism was developed aiming at a modelling study on dual fuel and blend fuel combustion in internal combustion (IC) engines fueled by gasoline/diesel and gasoline/biodiesel. Ignition delays were validated for 100% diesel, 100% gasoline and 100% biodiesel under 102 conditions in total. Subsequently, the validated reaction mechanism which consists of 107 species and 425 reactions was implemented in coupled KIVA4-CHEMKIN code. Three dimensional validations were further conducted under 3 conditions including pure diesel combustion, and gasoline/diesel DFM combustion with both single and double injection strategies in the engine. To investigate the fuel reactivity gradient, the gasoline/diesel DFM combustion with single injection was compared with other three hypothetical cases, one of which was DFM without fuel reactivity gradient, two were the blend fuel mode but with different start of injection (SOI) timings. The results showed that the fuel reactivity gradient could retard the ignition timing, reduce heat release rate, and ease peak pressure rise rate. In addition, low levels of NO x and soot emissions were observed for the DFM combustion. The gasoline/biodiesel reaction mechanism will be employed in future work.